2011
DOI: 10.1136/hrt.2010.210286
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of aortic root disease in Marfan syndrome: a systematic review and meta-analysis

Abstract: VSRR may represent a valuable option for patients with MFS with aortic aneurysm. However, this technique should be used with caution in patients with valve characteristics at risk for decreased durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
2
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 22 publications
(20 reference statements)
3
93
2
10
Order By: Relevance
“…Significant benefit of VSRR for thromboembolic complications have previously been demonstrated in meta-analysis (8,9), the latter study by Hu et al in 2014 (9) also favoured VSRR for endocarditis rates. Interestingly, Benedetto et al (8) reported a four-fold increased risk of intervention on aortic root with VSRR compared to CVG, a finding not supported by the present meta-analysis or by Hu et al This disparity may be explained by the greater sample sizes available in the more recent studies.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Significant benefit of VSRR for thromboembolic complications have previously been demonstrated in meta-analysis (8,9), the latter study by Hu et al in 2014 (9) also favoured VSRR for endocarditis rates. Interestingly, Benedetto et al (8) reported a four-fold increased risk of intervention on aortic root with VSRR compared to CVG, a finding not supported by the present meta-analysis or by Hu et al This disparity may be explained by the greater sample sizes available in the more recent studies.…”
Section: Discussioncontrasting
confidence: 53%
“…Flynn and colleagues have performed a systematic review and meta-analysis of studies on the surgical outcomes of VSRR versus traditional operation (Bentall operation) with valve prosthesis in patients with Marfan syndrome. The current meta-analysis is particularly important because since a previous analysis by Benedetto (8) in 2011 that questioned the efficacy of VSRR in this selective cohort of patients, several important papers have been published which have been included by Flynn and colleagues. Indeed, since then, Dr. David (15) published his experience with Marfan patients as well as the groups of Dr. Cameron (25) in Baltimore (US), Dr. Carrel (27) in Bern (Switzerland), Dr. Sievers (26) in Lubeck (Germany) and others.…”
Section: Expert Opinion 4 (Stefano Mastrobuoni and Gebrine El Khoury)mentioning
confidence: 99%
“…Несмотря на многие успеш-ные одноцентровые исследования, в среднесрочной перспективе после клапаносохраняющих операций долговечность нативного клапана остается неиз-вестной из-за недостаточного размера выборки. Недавно проведенный мета-анализ Benedetto U, et al показал, что пациенты с синдромом Марфана имели значительно больший риск повторной опера-ции после сохранения АоК, чем после операции Bentall DeBono [8]. Однако преимущества клапано-сохраняющих операций настолько очевидны, что попытки сохранить АоК при синдромах дисплазии соединительной ткани продолжаются вместе с раз-витием новых технологий [9].…”
Section: Long-term Results Of the Valve-saving Surgery In Marfan Syndunclassified
“…Паци-енты с протезированием имели большую частоту тромбоза и тромбоэмболических осложнений. Однако частота реопераций была выше у пациентов после клапаносохраняющих операций [8]. Распро-страненность структурных и неструктурных повре-ждений клапана в исследовании Coselli и Benedetto ставит под сомнение долговечность нативного АоК у пациентов с синдромом Марфана [8,9].…”
Section: Discussionunclassified
“…While aortic wall abnormalities have been described in inherited connective tissue disorders such as Marfan syndrome and bicuspid aortic valve disease, 52,53 recent reports indicate similar aortic involvement in classical congenital heart disease entities such as coarctation of the aorta, tetralogy of Fallot and transposition of the great arteries; MRI is central in defining the problem. 54 Pulmonary artery dilatation is seen with pulmonary valve abnormalities and connective tissue disease, but also occurs in association with bicuspid aortic valve, in the absence of a pulmonary valve abnormality, suggesting a primary vessel wall pathology predisposing to arterial dilatation.…”
Section: Arterial Abnormalities In Congenital Heart Diseasementioning
confidence: 99%